Blood doping: potential of blood and urine sampling to detect autologous transfusion. Issue 10 (24th April 2014) - Segura, J; Lundby, C
Abstract : The collection of blood, its storage as red blood cell (RBC) concentrates and its reinjection is prohibited; until now, the practice cannot be reliably detected. A recent innovation—the haematological module of the athlete's biological passport—can provide authorities with indications towards autologous blood transfusion. In situations where a given athlete has been exposed to altitude, heat stress, sickness, etc, additional evidence may be needed to establish beyond any reasonable doubt that a blood transfusion may actually have occurred. Additional evidence may be obtained from at least three different approaches using parameters related to blood and urine matrices.Genomics applied to mRNA or miRNA is one of the most promising analytical tools. Proteomics of changes associated with RBC membranes may reveal the presence of cells stored for some time, as can an abnormal pattern of size distribution of aged cells. In urine, high concentrations of metabolites of plasticisers originating from the blood storing bags strongly suggest a recent blood transfusion. We emphasise the usefulness of simultaneously obtaining and then analysing blood and urine for complementary evidence of autologous blood transfusion ('blood doping').